2008
DOI: 10.1007/s12031-008-9133-z
|View full text |Cite
|
Sign up to set email alerts
|

Circulating B7-H3(CD276) Elevations in Cerebrospinal Fluid and Plasma of Children with Bacterial Meningitis

Abstract: The objective of this study was to analyze the clinical significance of cerebrospinal fluid (CSF) and plasma concentrations of B7-H3, tumor necrosis factor-alpha (TNF-alpha), gamma interferon (IFN-gamma), and interleukin-17 (IL-17) in bacterial and aseptic meningitis in children. The participants were six children with bacterial meningitis, 16 with aseptic meningitis, and 12 control subjects. All participants were between 2 months and 12 years of age on admission. Cytokines determination was performed by enzym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 37 publications
(25 reference statements)
1
15
0
Order By: Relevance
“…Our previous work has shown that sB7-H3, released from monocytes, dendritic cells, and activated T cells, is detectable in the circulation of healthy humans (19). We also found that markedly increased levels of sB7-H3 were present in the serum samples from patients with bacterial meningitis when compared with healthy controls or patients with aseptic meningitis (23). In this study, we further demonstrated that patients diagnosed with sepsis, in contrast to healthy individuals, exhibited significantly elevated levels of sB7-H3 in their plasma, and more importantly, that plasma levels of sB7-H3 observed in the nonsurvivors of septic patients were substantially higher than those observed in the survivors.…”
Section: Discussionsupporting
confidence: 56%
“…Our previous work has shown that sB7-H3, released from monocytes, dendritic cells, and activated T cells, is detectable in the circulation of healthy humans (19). We also found that markedly increased levels of sB7-H3 were present in the serum samples from patients with bacterial meningitis when compared with healthy controls or patients with aseptic meningitis (23). In this study, we further demonstrated that patients diagnosed with sepsis, in contrast to healthy individuals, exhibited significantly elevated levels of sB7-H3 in their plasma, and more importantly, that plasma levels of sB7-H3 observed in the nonsurvivors of septic patients were substantially higher than those observed in the survivors.…”
Section: Discussionsupporting
confidence: 56%
“…Interestingly, native glioblastoma-derived soluble 4IgB7H3 suppresses NK lysis and enhances glioblastoma cell invasiveness in vitro. Insofar, our data let us to postulate that NK cell suppression and the proinvasive effect attributed to 4IgB7H3 expression in different tumor entities (37) are in fact exerted by membrane-bound and soluble B7H3, which was until now only evaluated for its diagnostic and prognostic capacity (22,23,38). Finally, as soluble 4IgB7H3 was sufficient to restore the invasiveness of 4IgB7H3-silenced LN-229 cells, the presence of a yet unknown counter-receptor must be postulated on glioblastoma cells, too.…”
Section: Discussionmentioning
confidence: 85%
“…Our recent clinical study did show significantly elevated levels of sB7-H3 in the circulation and cerebrospinal fluid of patients diagnosed with bacterial meningitis (23). Levels of cerebrospinal fluid and plasma sB7-H3 in these patients correlate with the intensity of their infectious inflammatory process and may also act as a useful marker for distinguishing bacterial from aseptic meningitis.…”
mentioning
confidence: 78%